Synergistic Effects of Water Hyacinth Compost on Vegetative Development of Forage Corn in Degraded Soils - Baluh Medyabrata Atmaja; Amelia Lulu Rosalin Hutabarat; Abdul Muta Ali; Wenni Meika Lestari; Alief Rahmania Safitri; Rifqi Hidayatulloh; Muhammad Irvan Ali; Muhammad Alfin (UNIVERSITAS ISLAM LAMONGAN, 2025)
Post-mining lands in Indonesia are characterized by severely degraded soils with low fertility, high acidity, and poor water retention, posing major challenges for agricultural rehabilitation. This study investigates the effect of water hyacinth (Eichhornia crassipes) compost at varying dosages (0%, 25%, and 50%) on early vegetative growth parameters of forage maize over a 30-day period. A randomized complete block design was used with six replications per treatment. Key growth indicators—plant height, stem diameter, and their respective growth rates—were measured and statistically analyzed. Results showed that the 50% compost treatment significantly increased plant height (51.87 cm) and height growth rate (1.73 cm/day) compared to lower dosages. Stem diameter parameters, while numerically improved, did not yield statistically significant differences. The improved growth is attributed to enhanced nutrient availability, microbial activity, and water retention due to compost application. These findings confirm that compost from invasive biomass can effectively improve degraded soils and initiate early crop development. The study contributes to sustainable land reclamation strategies and emphasizes that there must be long-term assessments of compost.